Self-sensing performance of MWCNT-low density polyethylene nanocomposites. (4th January 2018) - Gupta, Tejendra K; Kumar, S; Khan, Amal Z; Varadarajan, Kartik M; Cantwell, Wesley J
Abstract: Carbon nanotubes (CNTs) based polymer nanocomposites offer a range of remarkable properties. Here, we demonstrate self-sensing performance of low density polyethylene (LDPE)-multiwalled carbon nanotubes (MWCNTs) nanocomposites for the first time. The dispersion of the CNTs and the morphology of the nanocomposites was investigated using scanning electron microscopy, x-ray diffraction and Raman spectroscopic techniques. The thermal properties were measured using thermal gravimetric analysis and differential scanning calorimetry and were found to increase with increasing wt% of MWCNTs in LDPE matrix. An overall improvement in ultimate tensile strength, yield strength and Young's modulus was found to be 59.6%, 48.5% and 129.3%, respectively for 5.0 wt% loading of MWCNTs. The electrical percolation threshold was observed at 1.0 wt% of MWCNTs and the highest electrical conductivity of 2.8 × 10 −2 Scm −1 was observed at 5.0 wt% loading of MWCNTs. These piezo-resistive nanocomposites offer tunable self-sensing capabilities with gauge factors in the ranges of 17–52 and 42–530 in linear elastic (strain ∼3%) and inelastic regimes (strain ∼15%) respectively. Our demonstration would provide guidelines for the fabrication of low cost, self-sensing MWCNT-LDPE nanocomposites for potential use as civil water pipelines and landfill membranes.